Environmental Education and Climate Change in basic education: conceptions and practices - Fusinato, Bianca Georg; Riva, Poliana Barbosa da; Rodrigues, Karlen; Obara, Ana Tiyomi (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This paper aimed to identify the climate change conceptions of a group of students from basic education in order to, based on this data, develop actions of Environmental Education. The didactic sequence was conducted during the Science lessons for a 6th grade class of Elementary School, from a private school in Maringá (PR). To identify the previous conceptions about the environment and climate change, a diagnostic assessment was done, in which the students were able to express through texts and drawings their understandings on the topics in question. At this stage, the content analysis technique was used to interpret the answers. Next, during theoretical and practical lessons, were discussed the conceptions raised , the main concepts and processes linked to climate change, as well as the possible sustainable practices the school can embrace. The result of the study highlighted that the students had a simplistic view on the environment, since 82% of them associated the term, essentially, to nature and not one child considered the human being as a part of the environment. In addition, most of the students confused the concepts of “weather” and “climate”, as 67% of them stated, mistakenly, that the effects of climate change are temperature changes in a short period of time. In the end, it is possible to say that the discussions and practices in class promoted a redimensioning of the students’ views on climate change, expanding their knowledge and raising their awareness about local and global socioenvironmental challenges.